Potential distribution of three types of ephemeral plants under climate changes - Lan, Zhang; Huiliang, Liu; Hongxiang, Zhang; Yanfeng, Chen; Lingwei, Zhang; Kudusi, Kawushaer; Taxmamat, Dilxadam; Yuanming, Zhang (Frontiers in Plant Science, 2022)
Background Arid and semi-arid regions account for about 40% of the world’s land surface area, and are the most sensitive areas to climate change, leading to a dramatic expansion of arid regions in recent decades. Ephemeral plants are crucial herbs in this area and are very sensitive to climate change, but it is still unclear which factors can determine the distribution of ephemeral plants and how the distribution of ephemeral plants responds to future climate change across the globe. Aims Understanding the impact of climate change on ephemeral plant distribution is crucial for sustainable biodiversity conservation. Methods This study explored the potential distribution of three types of ephemeral plants in arid and semi-arid regions (cold desert, hot desert, and deciduous forest) on a global scale using the MaxEnt software. We used species global occurrence data and 30 environmental factors in scientific collections. Results Our results showed that (1) the average value of the area under the receiver operating curve (AUC) of each species was higher than 0.95, indicating that the MaxEnt model’s simulation accuracy for each species was good; (2) distributions of cold desert and deciduous forest species were mainly determined by soil pH and annual mean temperature; the key factor that determines the distribution of hot desert species was precipitation of the driest month; and (3) the potential distribution of ephemeral plants in the cold desert was increased under one-third of climate scenarios; in the hot desert, the potential suitable distribution for Anastatica hierochuntica was decreased in more than half of the climate scenarios, but Trigonella arabica was increased in more than half of the climate scenarios. In deciduous forests, the ephemeral plant Crocus alatavicus decreased in nearly nine-tenths of climate scenarios, and Gagea filiformis was increased in 75% of climate scenarios. Conclusions The potential suitable distributions of ephemeral plants in the different ecosystems were closely related to their specific adaptation strategies. These results contribute to a comprehensive understanding of the potential distribution pattern of some ephemeral plants in arid and semi-arid ecosystems.